Autoimmune rheumatic diseases and the risk of Parkinson disease: a nationwide population-based cohort study in Taiwan. (2nd January 2018) - Chang, Chi-Ching; Lin, Tzu-Min; Chang, Yu-Sheng; Chen, Wei-Sheng; Sheu, Jau-Jiuan; Chen, Yi-Hsuan; Chen, Jin-Hua
Abstract: Backgrounds: In autoimmune rheumatic diseases (ARDs), the levels of inflammatory mediators are increased and microglia may be activated, resulting in an inflammatory state and the degeneration of dopaminergic neurons. We investigated the association between ARDs and Parkinson disease (PD). Methods: We identified ARD patients through the Taiwan National Health Insurance Research Database from 2001 to 2012. From the general population, we randomly selected a comparison cohort that was frequency-matched by age (in 5-year increments), sex and index year. We analysed the risk of PD, stratified by sex, age and comorbidities, by using a Cox regression model. Results: The risk of PD was 1.37 times greater in ARD patients than in controls after adjustment for age, sex, and comorbidities. ARD subgroups, such as the rheumatoid arthritis and Sjogren syndrome (SS) cohorts, were associated with a significantly higher risk of PD (adjusted hazard ratio [HR], 1.14; 95% confidence interval [CI], 1.03–1.2 and adjusted HR, 1.56; 95% CI, 1.35–1.79, respectively). Furthermore, primary and secondary SS patients had significantly higher risks of PD (adjusted HR, 1.58; 95% CI, 1.32–1.88 and adjusted HR, 1.53, 95% CI, 1.23–1.90, respectively). Conclusions: The risk of PD was significantly higher in the ARD patients. Prospective studies are needed to confirm whether ARDs indeed increase the risk of PD.